Assessing the effect of Independent Prescribing for community optometrists and referral rates to Hospital Eye Services in Scotland - El-Abiary, Mariam (Eye (Lond), 2020)
INTRODUCTION: Since 2010, General Ophthalmic Services (GOS) legislation and Independent Prescribing (IP) enable community optometrists to manage primary eye conditions. No studies have assessed the effect of IP. We wished to determine the distribution of IP optometrists and associated hospital referral rates across Scotland. METHODS: In 2019, FOI requests (General Optical Council and NHS Education Scotland) identified all registered IP optometrists in Scotland and their registered postcodes. Data regarding community eye examinations and referrals to HES since 2010 were gathered via Information Services Division of NHS Scotland. RESULTS: As of March 2019, there were 278 IP optometrists in Scotland (278/1189; 23.4%). Two hundred eighteen IP optometrists work in 293 practices across 11 of Scotland’s 14 health boards. There was a strong correlation (r = +0.96) between population density and number of IP optometrists. Fifty-six percent of IP optometrists work in the two most deprived quintiles. Since IP’s introduction, there has been a marked increase in anterior segment supplementary visits (+290%). Optometry referrals to GPs have reduced by 10.5%, but referrals to HES have increased by 118% (to 96,315). There was no correlation between quantity of IP optometrists and referral rates to HES (r = −0.06, 95% CI −0.64 to 0.56, p = 0.86). CONCLUSIONS: This is the first analysis of IP optometrists and associated referral rates in Scotland. Despite good geographical distribution and increased supplementary attendances, optometric referrals to HES have doubled and continue to rise. We propose a ratio of primary, supplementary, non-referral and referral rates to discern the true impact of IP versus non-IP community optometric behaviour.